2010
DOI: 10.3892/or_00000800
|View full text |Cite
|
Sign up to set email alerts
|

PTEN inhibits the migration and invasion of HepG2 cells by coordinately decreasing MMP expression via the PI3K/Akt pathway

Abstract: Abstract. Hepatocellular carcinoma (HCC) is one of the most common malignant tumors. Most patients with HCC die within one year after diagnosis largely because of frequent tumor recurrence and metastasis. The tumor suppressor gene PTEN (phosphatase and tensin homolog deleted on chromosome 10) is one of the most commonly lost or mutated genes in a variety of human cancers, including HCC. PTEN antagonizes phosphoinositide-3-kinase (PI3K)/ATP-dependent tyrosine kinase (Akt) signaling, thereby negatively regulatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…HCC cells proliferate, invade, and metastasize through a variety of signaling pathways during tumor progression. 19 In the current study, we uncovered that HZC could promote the activation of the p38 MAPK pathway, then potentiating apoptosis of HepG2 cells and ultimately retarding the progression of HCC.…”
Section: Discussionmentioning
confidence: 72%
“…HCC cells proliferate, invade, and metastasize through a variety of signaling pathways during tumor progression. 19 In the current study, we uncovered that HZC could promote the activation of the p38 MAPK pathway, then potentiating apoptosis of HepG2 cells and ultimately retarding the progression of HCC.…”
Section: Discussionmentioning
confidence: 72%
“…Effects of flaccidoxide on the PI3K/AKT/mTOR/p70S6K pathway in BFTC-905 and T24 bladder cancer cells. Tian et al (31) showed that the PI3K/AKT/mTOR pathway is involved in cell proliferation, differentiation, survival and apoptosis. Therefore, we next investigated whether inhibition of the PI3K/AKT/mTOR pathway occurs in cells treated with flaccidoxide, which then prevents bladder cancer cell growth by triggering apoptosis.…”
Section: Resultsmentioning
confidence: 99%
“…13 A study showed that PTEN, as a crucial tumor suppressor, suppresses HepG2 cells growth, migration, and invasion in a PI3K/AKT-dependent manner. 31 The blockage of PTEN/PI3K/AKT was indicative of an antitumor effect of SEVO in Huh7 and HepG2 cells. Consequently, Dnmt3a silence emerged as a central mediator for the antitumor property.…”
Section: Discussionmentioning
confidence: 99%
“…Dnmt3a silences PTEN via DNA methylation . A study showed that PTEN, as a crucial tumor suppressor, suppresses HepG2 cells growth, migration, and invasion in a PI3K/AKT‐dependent manner . The blockage of PTEN/PI3K/AKT was indicative of an antitumor effect of SEVO in Huh7 and HepG2 cells.…”
Section: Discussionmentioning
confidence: 99%